Openness and Technological Innovations in Developing Countries: Evidence from Firm-Level Surveys - Almeida, Rita (2012)
This paper examines international technology transfers using firm-level data across 43 developing countries. Its findings show that exporting and importing activities are important channels for the transfer of technology. Majority foreign-owned firms are less likely to engage in technological innovations than minority foreign-owned firms or domestic firms. The authors interpret this finding as evidence that the technology transferred from multinational parents to majority-owned subsidiaries is more mature than that transferred to minority-owned subsidiaries. Their findings also suggest that foreign-owned subsidiaries rely mostly on the direct transfer of technology from their parents and that firms that import intermediate inputs are more likely to acquire new technology from their machinery suppliers.